Popcorn Brain: Familial Multiple Cerebral Cavernomatosis (Ictus, 2022)
Introduction. Cerebral vascular malformations are a heterogeneous group of disorders with several clinical manifestations. Cerebral Cavernous Malformations (CCM) are defined by dilated vascular spaces, with a single layer of endothelium, no mature vessel wall, and no intervening brain parenchyma. CCM may be sporadic or have an autosomal dominant hereditary pattern. Case Report. Here we present the case of a 31-year-old male with a medical history of multiple vascular malformations, difficult to treat epilepsy, and multiple hemorrhagic strokes. At initial evaluation the patient revealed mild dysarthria, left hemiparesis 4/5, hyperreflexia, left dysdiadochokinesia and dysmetria with a modified Rankin scale (mRS) score of 1. Magnetic Resonance Imaging (MRI) of the brain showed multiple supra and infratentorial parenchymal lesions with heterogeneous components on T1-weighted and T2-weighted sequences, surrounded by a rim of signal loss, demonstrating a “popcorn” appearance on Susceptibility-Weighted Angiography (SWAN) MRI. Molecular testing reported a heterozygous KRIT1 c.1099dup (p. His367Profs*3). Screening of fist degree relatives was performed, and antiepileptic treatment was adjusted. As of today, our patient has a mRS of 3, with refractary epileptic seizures. Conclusion. Symptomatic CCM must receive targeted medical treatment with a multidisciplinary approach. If a patient presents with more than one lesion, a familial case should be suspected, molecular testing and a screening head computed tomography should be done in first degree relatives. It is important to follow-up any patient with CCM with an annual MRI to monitor the size and number of lesions, symptomatic medical treatment is indicated, and surgical treatment should also be assessed.
Keywords: cavernoma; familial cavernomatosis; magnetic resonance imaging; structural epilepsy